2012
DOI: 10.1104/pp.112.200212
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Complex Extrachromosomal T-DNA Structures in Agrobacterium tumefaciens-Infected Plants      

Abstract: Agrobacterium tumefaciens is a unique plant pathogenic bacterium renowned for its ability to transform plants. The integration of transferred DNA (T-DNA) and the formation of complex insertions in the genome of transgenic plants during A. tumefaciensmediated transformation are still poorly understood. Here, we show that complex extrachromosomal T-DNA structures form in A. tumefaciens-infected plants immediately after infection. Furthermore, these extrachromosomal complex DNA molecules can circularize in planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 68 publications
2
56
0
Order By: Relevance
“…Tandem repeat junctions with short overlapping microhomology sequences at junctions between two T-DNA units exist in cotton (Zhang et al 2008), aspen (Kumar and Fladung 2000) and wild tobacco (Singer et al 2012). In our study, identity existed between the single joining nucleotides from the RB sequences and the filler DNA in T-DNA junctions in some of our recovered clones.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Tandem repeat junctions with short overlapping microhomology sequences at junctions between two T-DNA units exist in cotton (Zhang et al 2008), aspen (Kumar and Fladung 2000) and wild tobacco (Singer et al 2012). In our study, identity existed between the single joining nucleotides from the RB sequences and the filler DNA in T-DNA junctions in some of our recovered clones.…”
Section: Discussionmentioning
confidence: 53%
“…These data suggested that the formation of complex repeats in our transgenic plants potentially involved homologous recombination. Singer et al (2012) noticed the possible involvement of homologous recombination in the formation of circular T-DNA molecules in the plant transformation. In our study, homology between filler sequences in the junctions and plant genomic DNA existed in some clones (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…It is thus possible that T-strand conversion to dsT-DNA may be, at least in part, a limiting factor in T-DNA integration. Nevertheless, recent evidence suggests that dsT-DNA intermediates can undergo inter/intra-molecular cyclization and form circular molecules that may become incapable for integration 30 . Therefore, dsT-DNA formation and its accessibility to integration may be regulated in a more comprehensive manner.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one can use oligonucleotides such as triplex forming oligonucleotides (TFOs), short ssDNA or dsDNA donors such as T-DNA to induce HR. It should be noted that while T-DNA of Agrobacterium is iniltrated in the plant cell as a ssDNA coated by VirE2, it turns into dsDNA shortly after and probably integrates into the plant genome as dsDNA [19,20]. While unassisted HR levels are very low, and it is highly induced by speciic genomic DSBs [21].…”
Section: Principles Of Genome Editingmentioning
confidence: 99%